ANALISIS KREDIT BERMASALAH PADA PT. ADIRA DINAMIKA MULTIFINANCE TBK CABANG MANADO - SEMBIRING, JIMMY; SUMAMPOUW, HARRY J.; MANOPPO, WILFRIED S. (Sam Ratulangi University, 2016)
ABSTRACT: Rising incomes and business progress indirectly, affect the increased needs of the community and the funding source - the source of funds to meet their desires. One option to obtain funding is through financial institutions, namely Multifinance. One of the financial institutions that operate in the city of Manado and its surroundings are, PT. Adira Dinamika Multifinance Tbk, which is able to provide funding to meet the needs of the community, which is also the subject of our research. The objective of this study was to determine the extent of non-performing loans and the level of credit risk faced by the company. This research used quantitative descriptive analysis using financial ratios namely, Non Performing Loan (NPL) to determine the level of credit risk. The details of the Non Performing Loan PT. Adira Dinamika Multifinance Tbk Cabang Manado for the period 2013 to 2015 are as follows: 2013 NPL 0,0054%, 2014 NPL 0,0081%, 2015 NPL 0,0056%. From the details of the calculation of non-performing loan ratio in the period 2013 to 2015, namely: 0.0054% + 0.0081% + 0.0056% = 0.0191% Average - Average NPL = 0.0191 / 3 = 0.0063% Average level ratio - average NPL since the period 2013 - 2015 amounted to 0.0063% ratio is very good, because the level of credit risk is still low and is far from the level of Non Performing Loan tolerance set by Bank Indonesia, which amounted to 5%. This shows that the management of PT. Adira Dinamika Multifinance Tbk, Branch Manado excellent in credit management. Keywords: Credit Fluent, Non Performing